Evidence of Non-Corresponsive Causal Relationships Between Personality Traits and Social Power Over Time. (January 2017) - Wood, Dustin; Harms, P. D.
Although the effects of personality traits on social environments are regularly thought to mirror the effects of social environments on personality traits, the causal dynamics existing between personality traits and social power may represent an important exception. Using a sample of 181 fraternity and sorority members surveyed over a year, we show that agentic traits are more likely to show cross-sectional associations with social power, and may increase from the experience of social power. However, increases in social power over a year are predicted better by communal characteristics. The findings are consistent with the understanding that social power acts as a disinhibitor allowing people to enact their desires with less risk and greater efficacy, but is differentially afforded to individuals perceived as likely to promote the goals of others. We discuss the conditions that may need to exist for personality traits and environments to show corresponsive relationships more generally.